2020
DOI: 10.1136/postgradmedj-2020-139183
|View full text |Cite
|
Sign up to set email alerts
|

Serum pepsinogen levels and OLGA/OLGIM staging in the assessment of atrophic gastritis types

Abstract: BackgroundWe assessed the validity of using serum pepsinogen tests (sPGTs) to differentiate autoimmune atrophic gastritis (AAG) from environmental atrophic gastritis (EAG). We also investigated the correlation and prognostic value between disease stage, according to Operative Link for Gastritis Assessment (OLGA)/Operative Link on Gastric Intestinal Metaplasia Assessment (OLGIM), and sPGT results in patients with gastric atrophy.MethodsWe enroled 115 patients in this prospective study: 95 with atrophic gastriti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 25 publications
0
8
0
Order By: Relevance
“…Pepsinogen serology and APCA are also useful in the follow-up of AIG 111. Pepsinogen serology may differentiate autoimmune from H. pylori gastritis, also providing useful information on the clinical profiling of the most advanced atrophic stages 112. Serum pepsinogens are useful for detecting AIG in patients affected by autoimmune thyroiditis 113.…”
Section: Wg 2: Diagnosticsmentioning
confidence: 99%
“…Pepsinogen serology and APCA are also useful in the follow-up of AIG 111. Pepsinogen serology may differentiate autoimmune from H. pylori gastritis, also providing useful information on the clinical profiling of the most advanced atrophic stages 112. Serum pepsinogens are useful for detecting AIG in patients affected by autoimmune thyroiditis 113.…”
Section: Wg 2: Diagnosticsmentioning
confidence: 99%
“…Another feature is a consistent team of skilled endoscopists and a standardized biopsy protocol, particularly with endoscopists, histopathologists, investigators and patients blinded to the evaluation. Also, the primary outcome was assessed by combination of serum pepsinogen levels and OLGA/OLGIM stage[ 26 , 27 ].…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have shown that measuring serum levels of PGI, PGII, G17 and anti-H. pylori antibodies can be used to diagnose atrophic gastritis and intestinal metaplasia [36][37][38][39]. A study from Turkey showed that the PG1/PG2 ratio may be useful to identify both autoimmune and environmental atrophic gastritis [40]. A Japanese group showed that high G17 and low PG I/II ratios could be used to identify AIG in a cross-sectional cohort of patients undergoing upper endoscopy [41].…”
Section: Discussionmentioning
confidence: 99%